2005
DOI: 10.1590/s1678-97412005000400010
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[Myocardial metabolism after hypothermic retrograde continuous blood cardioplegia with anterograde warm cardioplegic induction]]>

Abstract: Metabolismo miocárdico após cardioplegia sangüínea hipotérmica retrógrada contínua com indução anterógrada normotérmica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, we are not able to explain how the myocardium may use lactate without a corresponding increase in oxygen utilization. Sobrosa et al ( 10 ) found positive gradients between arterial blood lactate and blood from the coronary sinus, concomitantly with a minimum difference between the SO 2 of arterial blood and the blood from the coronary sinus in patients undergoing CABG with cardiopulmonary bypass at the time of reperfusion.…”
Section: Discussionmentioning
confidence: 98%
“…However, we are not able to explain how the myocardium may use lactate without a corresponding increase in oxygen utilization. Sobrosa et al ( 10 ) found positive gradients between arterial blood lactate and blood from the coronary sinus, concomitantly with a minimum difference between the SO 2 of arterial blood and the blood from the coronary sinus in patients undergoing CABG with cardiopulmonary bypass at the time of reperfusion.…”
Section: Discussionmentioning
confidence: 98%
“…The main principles of myocardial protection are reduction of metabolic activity by hypothermia and therapeutic arrest of the electrical activity and contractile apparatus of the myocytes by administering cardioplegic solution ( e.g. , depolarization of the membrane potential by high potassium blood cardioplegia [ 1 - 3 ] .…”
Section: Introductionmentioning
confidence: 99%